Precision punching on laminates composite panel: effect of dual-stages puncher. (2015) - Chan, H.Y.; Abdullah, A.B.; Samad, Z.; Zain, M.S.M.
This study aims to investigate the effect of dual-stage puncher to the punched hole quality of a laminate composite panel. For this purpose, two sets of punchers were fabricated and the punching process was carried out using universal testing machine. The images of the punched holes are scanned using a high-resolution camera, and then the holes are analysed using the developed algorithm based on image processing technique. Quality is measured based on complete shearing and roundness of the hole top and bottom surface. Results show that dual-stages puncher, which allow for lower die clearance, indicate better in terms of accuracy of the punched hole. In addition, it may decrease the required load to implement the operation.